2013
DOI: 10.1021/ja402598k
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Electrochemical Aggregative Growth Mechanism

Abstract: The early stages of nanocrystal nucleation and growth are still an active field of research and remain unrevealed. In this work, by the combination of aberration-corrected transmission electron microscopy (TEM) and electrochemical characterization of the electrodeposition of different metals, we provide a complete reformulation of the Volmer-Weber 3D island growth mechanism, which has always been accepted to explain the early stages of metal electrodeposition and thin-film growth on low-energy substrates. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
177
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(201 citation statements)
references
References 57 publications
18
177
1
2
Order By: Relevance
“…1a) the nucleation maximum is preceded by a pronounced current decay at low deposition times. Similar decaying current transients at deposition times exceeding those characteristic of the double layer charging, have also been reported in the literature [20,33,34]. Analysis of the deposition transients for Pt (IV) in logarithmic coordinates (Fig.…”
Section: Deposition Kineticssupporting
confidence: 84%
See 1 more Smart Citation
“…1a) the nucleation maximum is preceded by a pronounced current decay at low deposition times. Similar decaying current transients at deposition times exceeding those characteristic of the double layer charging, have also been reported in the literature [20,33,34]. Analysis of the deposition transients for Pt (IV) in logarithmic coordinates (Fig.…”
Section: Deposition Kineticssupporting
confidence: 84%
“…Recently, Ustarroz proposed the so-called "generalized electrochemical aggregative growth mechanism" [33], comprising nucleation of metal clusters, their growth to a critical (limited by adsorption) size, followed by their surface diffusion, aggregation, coalescence, and recrystallization. Since, diffusion on the support surface must depend on its type and topography, the similarity of the deposition transients on the GC and HOPG supports in this We assume that secondary crystals nucleate at the surface of Pt particles, whose primary growth beyond a certain size is hindered by adsorption of either chloride ions (in this work at potentials E d > 0.060 V vs. RHE), or hydrogen adatoms (E d < 0.060 V vs. RHE when the H UPD coverage is high).…”
Section: Mechanistic Aspects Of Pt Electrodeposition On Carbon Substrmentioning
confidence: 99%
“…30 Such features are abundant on the ZYB grade HOPG used, but absent from the TEM grid, which may explain the slower kinetics that are evident when the TEM grid is used as the electrode. The TEM images acquired in this study suggest that an aggregative mechanism operates in the electrochemical nucleation and growth of metal NPs, 13,27,28 wherein NPs form and aggregate into larger nanostructures. Assuming that all nanostructures are generated from NPs, which is reasonable based on the TEM images, and that all NPs have spherical shapes, N0 can also be estimated from the total charge of the reduction current-time curves according to equation (1):…”
Section: Experimental Methodsmentioning
confidence: 75%
“…[33,36] Electrodeposition performed on TEM grids by Ustarroz et al has shown that the nucleation sites originate from the assembly of tiny mobile subnuclei. [37] Therefore, the fact that experiments performed in magnetic fields produce a larger number of particles would imply that the early nuclei are somehow stabilized by the field, with growth setting in before they are able to assemble. The physical basis of this magnetic influence on nucleation is not clear, although the subsequent growth may be influenced by micro-MHD, as suggested by Aogaki.…”
Section: Accepted Manuscriptmentioning
confidence: 99%